Analisis Dampak Gangguan Aircraft Rotation terhadap Kelancaran Operasional Keberangkatan Pesawat di Area Airside: Studi pada AOCC Bandara Sultan Aji Muhammad Sulaiman Sepinggan Balikpapan - Siti Aisyah; Rosiana Ulfa (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Aircraft rotation disruption is one of the operational problems that can affect the smoothness of aircraft departure operations in the airside area. Such disruptions may cause flight delays, apron congestion, and decrease On Time Performance (OTP). Under these conditions, the Airport Operations Control Center (AOCC) plays an important role as the operational coordination center in controlling and minimizing the impact of operational disruptions. This study aims to identify the forms of aircraft rotation disruptions, analyze their impact on the smoothness of aircraft departure operations, and determine the efforts undertaken by AOCC in handling aircraft rotation disruptions at Sultan Aji Muhammad Sulaiman Sepinggan Airport Balikpapan. This research uses a qualitative method with primary data sources and secondary data. Primary data was obtained through interviews with 5 sources, observations, and documentation, while secondary data was obtained from operational documents, literature, and other supporting data. The research was carried out at AOCC Sultan Aji Muhammad Sulaiman Sepinggan Balikpapan Airport in August 2025 to April 2026. The results showed that aircraft rotation disruptions included late arrival aircraft, technical aircraft problems, delays in ground handling processes, weather conditions, flight slot limitations, and operational resource constraints. These disruptions affected operational performance by reducing On Time Performance (OTP), increasing apron congestion, extending parking stand utilization, and increasing the complexity of operational coordination. AOCC handled these disruptions through real-time operational monitoring, cross-unit coordination, turnaround optimization, parking stand adjustments, and the implementation of rescheduling and retiming to minimize the impact of delays on flight operations.